Analysis of MSMEs Marketing Strategies and Competitiveness on Increasing Sales in the Digital Era at MSMEs Tofu in Sukabumi City - Elisa Fitria; Erry Sunarya; Resa Nurmala (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the influence of marketing strategies and competitiveness on sales performance in the digital era among tofu MSMEs (Micro, Small, and Medium Enterprises) in Sukabumi City. The main issues faced by these businesses include the suboptimal use of digital marketing strategies and low competitiveness amid increasingly intense market competition driven by technological advancement. This research adopts a quantitative method with associative and descriptive approaches, utilizing multiple linear regression analysis to examine the relationship between marketing strategy (X1), competitiveness (X2), and digital-era sales performance (Y). Data were collected through questionnaires distributed to 54 tofu MSME actors using a saturated sampling technique. The findings indicate that both marketing strategies and competitiveness have a positive and significant effect on sales performance in the digital era. Therefore, improving product quality, conducting effective promotional activities, and enhancing operational efficiency and flexibility are essential in strengthening competitiveness and boosting sales among tofu MSMEs in Sukabumi.